2012
DOI: 10.1590/s0102-79722012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Inductive Reasoning Test for Children - IRTC

Abstract: This study aimed to search for validity and reliability evidences for 'A and B Forms' of the Inductive Reasoning Test for Children -IRTC. A total of 417 students, both sexes, from 1 st to 5 th grade, between 6 and 11 years old participated of the study. 'A Form' was administered to 219 children and 'B Form' to 198. The investigation of the internal structure of both forms indicated that the correlations between the items may be explained by a single factor which is understood as inductive reasoning. Appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…These studies have demonstrated that inductive reasoning capacity develops significantly grade by grade, with the most rapid improvement occurring in middle school (e.g. Csapó, 1997;Díaz-Morales & Escribano, 2013;Molnár et al, 2013;Muniz et al, 2012;. Several empirical studies have shown that inductive reasoning is closely tied to problem-solving skills (Csapó, 1997;Molnár et al, 2013;Schweizer et al, 2013) and plays an important role in learning most school subjects, such as mathematics (Nunes & Csapó, 2011), science (Adey & Csapó, 2012;Hamers et al, 1998) and other subjects (Nikolov & Csapó, 2018;Soodmand Afshar et al, 2014).…”
Section: Inductive Reasoning and Science Motivationmentioning
confidence: 99%
“…These studies have demonstrated that inductive reasoning capacity develops significantly grade by grade, with the most rapid improvement occurring in middle school (e.g. Csapó, 1997;Díaz-Morales & Escribano, 2013;Molnár et al, 2013;Muniz et al, 2012;. Several empirical studies have shown that inductive reasoning is closely tied to problem-solving skills (Csapó, 1997;Molnár et al, 2013;Schweizer et al, 2013) and plays an important role in learning most school subjects, such as mathematics (Nunes & Csapó, 2011), science (Adey & Csapó, 2012;Hamers et al, 1998) and other subjects (Nikolov & Csapó, 2018;Soodmand Afshar et al, 2014).…”
Section: Inductive Reasoning and Science Motivationmentioning
confidence: 99%
“…Os dados apresentados também podem ser considerados de acordo com Almeida e colaboradores (2008), segundo os quais, nota-se, de modo geral, forte influência da escolarização nas diferentes aptidões cognitivas, bem como no desempenho em testes de inteligência, inclusive naqueles relacionados à inteligência fluida. Outros estudos também enfatizam o aumento significativo no desempenho nas habilidades cognitivas em crianças e adolescentes relacionado à escolarização (Muniz, Seabra & Primi, 2012;Nakano, 2012;Primi, Couto, Almeida, Guisande & Miguel, 2012;Queiroz, Enumo & Primi, 2013;Wechsler & Schelini, 2006).…”
Section: Discussionunclassified
“…An example of the importance of psychometric and cognitive models both being used, as much in construction as in the understanding of a reasoning test, can be seen in the study of Muniz, Seabra and Primi (2012). The authors constructed items of an inductive reasoning test based on the theory of Josef Klauer (1990), which identifi ed six paradigms for inductive reasoning and specifi c tasks for each of them.…”
Section: Discussionmentioning
confidence: 99%